Reinforced in-situ concrete drain / Nor Auni Saadiah Mohamad Ansor - Mohamad Ansor, Nor Auni Saadiah (Universiti Teknologi MARA, Perak, 2014)
This report briefly describes how to construct a reinforcement in-situ concrete drain. The objective of this report is to identify the machinery and tools used in the construction of reinforced drains and also to investigate the problems and solutions of the drains. It is produced based on the experience of five months at the project site. Observation has been made by site visit to the project site. In addition, it also can interview a person who is experienced in the work of construction in-situ drain such as site supervisors, contractors. It involves many parties and construction processes are very complicated. During the construction process being carried out some of the problems related with a construction method of the drains and get solve problems that have been identified. In conclusion, this report will describe in more detail about the method how to construct a reinforcement drain. Hope that this report can give a lot of advantages how the construction of reinforced in-situ concrete drain and the machinery and tool used for construction an in-situ drain also the maintenance in-situ drain.